1999
DOI: 10.1038/sj.onc.1202263
|View full text |Cite
|
Sign up to set email alerts
|

Functional association of TGF-β receptor II with cyclin B

Abstract: Utilizing the cytoplasmic tail of Transforming Growth Factor Receptor Type II (TGFb RII) as bait in a yeast two hybrid system, we have identi®ed human cyclin B2 as a direct physical partner of TGFb RII. Analysis of deletion mutants of glutathione-S-transferase (GST)-cyclin B2 mapped its binding domain for TGFb RII to the C-terminal and revealed a negative regulatory region immediately upstream of the cyclin box. Using recombinant proteins, Cdc2 was demonstrated to indirectly interact with TGFb RII via cyclin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 40 publications
1
27
0
1
Order By: Relevance
“…More interestingly, we found CCNB2 was induced by SMAD4-silencing. A major TGF-β receptor in TGF-β/SMAD signaling pathway, TGFBR2, could bind CCNB2 for indirectly interacting with CDK1, which lead to CDK1 inactivation and cell cycle arrest in the G1/S for preventing the cells entry into the G2/M phase (Liu et al 1999). Our results showed that silencing of SMAD4 increased the expression of CDK1 and CCNB2 but decreased the levels of LOC100038019 (TGFBR2), suggested that downregulated TGFBR2 levels might not cause cell-cycle arrest in the G1/S phase, thus confirming that the progression of cell cycle induced by silencing of SMAD4 mainly occurred in the G2/M phase.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, we found CCNB2 was induced by SMAD4-silencing. A major TGF-β receptor in TGF-β/SMAD signaling pathway, TGFBR2, could bind CCNB2 for indirectly interacting with CDK1, which lead to CDK1 inactivation and cell cycle arrest in the G1/S for preventing the cells entry into the G2/M phase (Liu et al 1999). Our results showed that silencing of SMAD4 increased the expression of CDK1 and CCNB2 but decreased the levels of LOC100038019 (TGFBR2), suggested that downregulated TGFBR2 levels might not cause cell-cycle arrest in the G1/S phase, thus confirming that the progression of cell cycle induced by silencing of SMAD4 mainly occurred in the G2/M phase.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, expression of cyclic D1 and cdk4, which are essential for cell cycle progression, is downregulated (Ewen et al, 1993;Ko et al, 1998), whereas transcription of genes coding for collagen and other extracellular matrix proteins is enhanced (Roberts et al, 1990). Moreover, TGFbRII seems to cooperate directly with cell cycle proteins, such as cyclin B, representing an additional way to inhibit cell proliferation (Liu et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The prominent function of TGF-␤ in tumor suppression as well as cellular differentiation is through cell cycle regulation (Liu, 2006). Various TGF-␤-regulated molecules have been identified with functions that principally govern G1 progression (Massague, 2004;Liu, 2006), whereas some mitotic players, including cyclin B and CDC2, are also implicated as targets of TGF-␤ signaling during the cell cycle (Choi et al, 1999;Liu et al, 1999;Wan et al, 2001). Recent studies addressing Smad3 function in cells of the hematopoietic system have revealed that knockout of Smad3 in mice results in a significant accumulation of a G2/M population of bone marrow stromal cells (BMSCs) (Epperly et al, 2006).…”
Section: Introductionmentioning
confidence: 99%